New frontiers in genetic testing and screening - University of Minnesota: Center for Bioethics (University of Minnesota, Center for Bioethics, 1999)
We often hear that we are witnessing a "genetic revolution" that will profoundly effect our health care in the near future. One of the first fruits of this revolution is the availability of genetic tests able to detect inherited disorders, and even predispositions to develop many diseases that traditionally have not been viewed as genetic in origin. These developments raise a number of questions deserving our careful attention.
A reading packet on new frontiers in genetic testing and screening.
Keywords: Genetics; Genetics, Medical; Genetic Screening